PENGUJIAN AKTIVITAS DAYA ANALGETIK EKSTRAK n-HEKSANA, ETIL ASETAT DAN ETANOL DAUN KANGKUNG PAGAR (Ipomoea carnea Jacq) - Qurotulaeni, Engkun; Setyahadi, Siswa; Simajuntak, Partomoan (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Pain is unpleasant symptom and feeling in of the organs, caused by tissue damage such as inflammatory conditions, infection, or related to muscle spasms. Previous research, is known that leaves Ipomoea carnea can inhibit prostaglandins which are pain mediators. This research aims to determine the activity of analgesic leaves Ipomoea carnea. The leaves Ipomoea carnea macerated with 96% ethanol and partitioned with n-hexane and ethyl acetate. The three extracts tested on male white mice (Mus musculus) with a weight of 25-30 g. The research method used is the writhing test. The test animals were divided into 11 groups. Group 1 (Na CMC 0.5% positive control), Group 2 (Paracetamol as a comparison), Group 3-5 (Ipomoea carnea ethanol extract doses of 50 mg, 100 mg and 200 mg/Kg BW), Groups 6-8 (ethyl acetate extract of Ipomoea carnea leaves doses of 50 mg, 100 mg and 200 mg/kb BW) and groups 9-11 (n-hexane extract of Ipomoea carnea leaves dose 50 mg, 100 mg and 200 mg/kb BW). The pain inducer 0.5% acetic acid intraperitoneally. Observations were carried out for 1 hour every 5 minutes and the percentage of analgesic power was calculated. Ethanol extract provides effect than ethyl acetate and n-hexane extracts, dose of 50 mg/Kg BW 62.4%; 100 mg/Kg BW 70.42% and 200 mg/Kg BW 69.15%. The significant value of the Mann-Whitney test is 0.008 from the test sample against the positive control so it can be concluded that there is analgesic activity from the ethanol extract of Ipomoea carnea leaves.